Comparison of fatigue crack propagation behaviour in two steel grades S235, S355 and a steel from old crane way - Seitl, Stanislav; Pokorný, Pavel; Miarka, Petr; Klusák, Jan; Kala, Zdeněk; Kunz, Ludvík (EDP Sciences, 2020)
Utilization of various steel grades in civil engineering allows designing bridges, bridge elements or simple structures according to their fracture mechanical properties. The service intervals of structures, which are going to be in use for a long time, cannot be calculated only on the basis of tensile and brittle fracture properties but also on the knowledge of the resistance to the fatigue crack growth. This contribution presents a comparison of the fatigue behaviour of two modern steel grades S235 J2, S355 J2 and a steel extracted from an old crane way. The comparison of these steel grades is done by fatigue crack propagation tests (the results of the experimental tests are described using concept of the stress intensity factor range K). The fatigue properties are discussed and recommendations for the use of the steels are stated.

Utilization of various steel grades in civil engineering allows designing bridges, bridge elements or simple structures according to their fracture mechanical properties. The service intervals of structures, which are going to be in use for a long time, cannot be calculated only on the basis of tensile and brittle fracture properties but also on the knowledge of the resistance to the fatigue crack growth. This contribution presents a comparison of the fatigue behaviour of two modern steel grades S235 J2, S355 J2 and a steel extracted from an old crane way. The comparison of these steel grades is done by fatigue crack propagation tests (the results of the experimental tests are described using concept of the stress intensity factor range K). The fatigue properties are discussed and recommendations for the use of the steels are stated.
Comparison of fatigue crack propagation behaviour in two steel grades S235, S355 and a steel from old crane way
Keywords: fatigue; fatigue